Named data network dynamic cache placement strategy based on programmable data plane. Issue 1 (21st October 2022) - Hou, Saifeng; Hu, Yuxiang; Tian, Le
Abstract: Aiming at the efficiency and implementation of in‐network cache in Named Data Network, an in‐network cache method based on the programmable data plane was proposed. Set the cache port on the programmable data plane, when the cache policy determined that the content needs to be cached, set the output port as the cache port and forward it to the cache unit for caching. According to the different requirements of different contents on Quality of Service, the request contents were classified. And the cache probability of classified contents was calculated based on the content popularity and the cache cooperation information between nodes. The cache threshold was dynamically set according to the state of cache space occupancy and compared with the cache probability to determine whether to cache the contents. Experimental results show that the proposed cache placement strategy can effectively improve the cache hit ratio and reduce the average transmission latency compared with the traditional cache placement strategy. Abstract : A dynamic cache placement strategy is proposed to classify content according to whether is a need for retransmission. And the dynamic cache placement strategy and data plane forwarding function are realized by using the programmable language.